2001
DOI: 10.1242/dev.128.4.571
|View full text |Cite
|
Sign up to set email alerts
|

Eph signalling functions downstream of Val to regulate cell sorting and boundary formation in the caudal hindbrain

Abstract: Rhombomeres are segmental units of the developing vertebrate hindbrain that underlie the reiterated organisation of cranial neural crest migration and neuronal differentiation. valentino (val), a zebrafish homologue of the mouse bzip transcription factor-encoding gene, kreisler, is required for segment boundary formation caudal to rhombomere 4 (r4). val is normally expressed in r5/6 and is required for cells to contribute to this region. In val(−) mutants, rX, a region one rhombomere in length and of mixed ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…This progressive establishment of cell segregation mechanisms during hindbrain segmentation reflects the fact that Eph receptors and ephrins, which restrict intermingling, are regulated downstream of TFs that underlie segmentation. For example, Epha4 is a direct target of Krox20 (Theil et al, 1998) and is repressed by Hoxa3 and Hoxb4 (Prin et al, 2014); Ephb4 is regulated downstream of Kreisler (Cooke et al, 2001), and ephrin B2 (Efnb2) is regulated by Hoxb4 and Hoxd4 (Prin et al, 2014). Consistent with this, some isolated Krox20-expressing cells are observed in r2+r4+r6 during the period of border sharpening (Cooke and Moens, 2002;Irving et al, 1996) (Fig.…”
Section: Generation Of Sharp and Homogeneous Hindbrain Segmentssupporting
confidence: 67%
See 2 more Smart Citations
“…This progressive establishment of cell segregation mechanisms during hindbrain segmentation reflects the fact that Eph receptors and ephrins, which restrict intermingling, are regulated downstream of TFs that underlie segmentation. For example, Epha4 is a direct target of Krox20 (Theil et al, 1998) and is repressed by Hoxa3 and Hoxb4 (Prin et al, 2014); Ephb4 is regulated downstream of Kreisler (Cooke et al, 2001), and ephrin B2 (Efnb2) is regulated by Hoxb4 and Hoxd4 (Prin et al, 2014). Consistent with this, some isolated Krox20-expressing cells are observed in r2+r4+r6 during the period of border sharpening (Cooke and Moens, 2002;Irving et al, 1996) (Fig.…”
Section: Generation Of Sharp and Homogeneous Hindbrain Segmentssupporting
confidence: 67%
“…Eph receptors and ephrins that have a high affinity are expressed in complementary hindbrain segments, and consequently bidirectional signalling occurs at segment borders. For example, in zebrafish, this is seen for Epha4 and Efnb3, and for Ephb4 and Efnb2a (Chan et al, 2001;Cooke et al, 2001;Xu et al, 1995) (Fig. 5A).…”
Section: Roles and Mechanisms Of Cell Segregationmentioning
confidence: 89%
See 1 more Smart Citation
“…For example, in the zebrafish hindbrain, expression of EphB4 in r2, r5, and r6 is complementary to ephrinB2 in r1, r4, and r7, and expression of EphA4 in r3 and r5 is complementary to ephrinB3 in r2, r4, and r6, as well as to ephrinB2 ( Figure 1B ). There is extensive evidence that signalling through these Eph receptors and ephrins underlies the sharpening of segment borders in the hindbrain ( Xu et al, 1995 ; Xu et al, 1999 ; Cooke et al, 2001 ; Cooke et al, 2005 ; Kemp et al, 2009 ; Sela-Donenfeld et al, 2009 ; Calzolari et al, 2014 ; Cayuso et al, 2019 ). Studies of cell segregation and border formation in vivo have found a dominant role of Eph receptor forward signalling through kinase-dependent pathways ( Cayuso et al, 2019 ; O'Neill et al, 2016 ; Rohani et al, 2014 ), although reverse signalling through ephrinBs could also contribute ( Wu et al, 2019 ).…”
Section: Mechanisms Of Eph-ephrin Signalling In Cell Segregationmentioning
confidence: 99%
“…A model for how cells segregate to form sharp segment borders in the hindbrain can be proposed based on analyses of Eph-ephrin function in other tissues, summarised above, together with studies in the hindbrain itself. The initial ragged border of hindbrain segments is transformed into a sharp and straight border through a combination of cell identity regulation ( Zhang et al, 2012 ; Addison et al, 2018 ) and Eph-ephrin-mediated cell segregation ( Xu et al, 1995 ; Xu et al, 1999 ; Cooke et al, 2001 ; Cooke et al, 2005 ; Kemp et al, 2009 ; Calzolari et al, 2014 ; Cayuso et al, 2019 ). Cell segregation is likely driven by increased cortical tension at the heterotypic interface, principally through Eph receptor forward signaling ( Cayuso et al, 2019 ) that acts through ROCK and MLCK to increase actomyosin contraction.…”
Section: Summary and Perspectives On Border Sharpening In The Hindbrainmentioning
confidence: 99%